LEGAL REVIEW OF ODONTOGRAM MEDICAL RECORDS AS AN IDENTIFICATION TOOL IN LEGAL EVIDENCE IN COURT - Erdi Effendi Nasution; Marice Simarmata; Muhammad Arif Sahlepi (RADJA PUBLIKA, 2025)
Odontogram medical records play a role in documenting dental and oral conditions as a basis for establishing a diagnosis, treatment planning, and legal evidence in medical disputes. This study aims to analyze the legal regulations regarding odontogram medical records as part of medical documents according to Indonesian law, the evidentiary power of odontogram medical records as a means of identification in the judicial process, and the legal responsibility of medical personnel for the validity of odontogram medical records in legal evidence in court. This study uses a normative juridical study type. This study is descriptive and analytical using various types of secondary data and is analyzed deductively qualitatively. The study findings indicate that the legal regulations for odontogram medical records in Indonesia are regulated in Law No. 17 of 2023 concerning Health along with Government Regulation No. 28 of 2024 and Minister of Health Regulation No. 24 of 2022 concerning Electronic Medical Records emphasizes the aspects of completeness, accuracy, security, and data integration. The evidentiary power of odontogram medical records as an identification tool in the judicial process to provide objective, specific, and verified scientific information regarding a person's identity through the condition of the teeth and oral cavity.